FeCl3 as a low-cost and efficient p-type dopant of Spiro-OMeTAD for high performance perovskite solar cells. Issue 17 (5th March 2018) - Gu, Xiaoyu; Li, Yang; Mu, Yanfei; Zhang, Min; Lu, Tongbu; Wang, Peng
Abstract : We have employed low-cost FeCl3 as efficient dopant of Spiro-OMeTAD for high performance perovskite solar cells. Abstract : Chemical doping is a viable tactic to improve the charge transporting properties of organic semiconductors in efficient perovskite solar cells. In this paper, we first employ the low-cost inorganic salt FeCl3 as a chemical dopant to replace the traditional expensive cobalt complex for the oxidization of 2, 2′, 7, 7′-tetrakis( N, N-p -dimethoxyphenylamino)-9, 9′-spirobifluorene (Spiro-OMeTAD), a typical organic hole-transporter. Based on the joint measurements of electron absorption spectra, cyclic voltammetry, and the hole-only device, we reveal that FeCl3 can effectively oxidize Spiro-OMeTAD and improve the hole transporting properties of Spiro-OMeTAD. Through carefully optimizing the dopant concentration, solar cells with 80% FeCl3 doped Spiro-OMeTAD achieve over 17% power conversion efficiency based on a triple cation perovskite photoactive layer, which is comparable to that of devices with a classical cobalt complex dopant. Our work demonstrates the potential of using FeCl3 as a low-cost chemical dopant for hole-transporting materials in perovskite solar cells.